Red cell alloimunization and autoantibodies in transfusion dependent thalassemia patients of Jammu region - Dutt, Neeti; Sharma, Sushil; Sidhu, Meena (International Journal of Advances in Medicine, 2022)
Background: Thalassemia is one of the most common genetic disorder of hemoglobin synthesis in Jammu region. Although RBC transfusion is life saving for these patients, it may be associated with some complications like RBC alloimmunization. Thus, alloimmunization against red blood cell antigens increases the need for transfusion and can significantly complicate transfusion therapy. Therefore, screening for unexpected antibodies should be a part of all pretransfusion testing, with antibody identification in the event of a positive result. The aim of the study was to determine the frequency of alloimmunization and autoimmunization and the most common alloantibodies involved. Methods:This was a descriptive study involving a total of 146 thalassemic patients in the age range of 2-32 years receiving regular blood transfusions, registered at SMGS blood bank, Jammu. Antibodies screening, antibody identification, and cross matching was done on all patient samples included in the study, during the period between November 2014 and October 2015. Results: At the start of the study, 8 patients who tested positive for alloantibodies 3 patients had more than one antibody subtype. Anti-E was the commonest antibody found in 4 (50%) patients. Similarly, at the end of study, antibody screening and then identification revealed presence of antibodies in 10 patients. Only 1 patient had more than one antibody subtype. Anti E was again the commonest antibody found in 5 (50%) patients. Conclusions:The most common alloantibodies identified were anti Rh system antibodies (anti-E and anti-D) followed by Kell antibodies. In order to reduce alloimmunization, a policy for performing extended red cell phenotyping of these patients is essential and at least antigen E and Kell negative blood should be provided for transfusion to these patients.